Childhoods and psychoanalysis in Uruguay from 1955 to 1984 - Fernández Caraballo, Ana María (2023)
This article aims to give an account of the ideas about childhood linked to psychoanalysis, more specifically to psychoanalysis with children, from 1955 to 1984. It seeks to unravel what conceptions about children and childhood emerge from psychoanalysis read, interpreted and conceptualized in Uruguay. It is a historical-discursive study or historicity (Foucault, 1969) that allows the analysis of documents (articles, case histories and clinical reports) coming from psychoanalytic theories and practices. It is interesting to visualize Uruguayan traits (Ginzburg, 1994) and singularities about these ideas, their theorizations, and their underlying practices. The dates studied, which span from 1955 to 1984, cover periods related to the consolidation of “official” psychoanalytic institutions (such as the APU, AUDEPP, Freudian School of Psychoanalysis and the ELP), the entry of psychoanalysis into the University, and the period corresponding to the civil-military Dictatorship, exclusion, and formation of “unofficial” study groups. In general terms, since the decade of the sixties, it is clearly observed how psychoanalysis with children, adolescents, and families, includes a variety of theoretical and practical proposals that are preserved until the present, coexist and, on some occasions, are used in a mixture of theories without epistemological discussion, just as, on other occasions, theories and practices are discussed and compete.